The Effect Of Chromium (Cr) Alloying Addition On The Microstructure Of Titanium Aluminides Alloys Related To Its Oxidation Behaviour. - Manalu, Okti J. P.; Astrawinata, Rizal; Mohd. Sharif, Nurulakmal (2005)

(untitled)
A number of selected compositional variations of titanium aluminides alloys have been produced by arc melting process in a specially-designed and locally made furnace.